Les assureurs et les réassureurs face aux échéances du marché unique - Biagosh, Axel (Assurances, 1990)
With the advent of a single European common market, insurers and reinsurers have quite a task on hand. We are grateful to Dr. Axel Biagosh for allowing us to publish the speech he delivered at the September Rendez-Vous 1989 in Monte-Carlo. According to the author, the markets in Europe will undoubtedly change, specifically as a result of decisions made by the European Court. While these decisions will technically only affect a few countries, they will be of paramount importance for the insurance business.